2020
DOI: 10.1002/srin.201900511
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐Based Additive Manufacturing of WC–Co with High‐Temperature Powder Bed Preheating

Abstract: The field of additive manufacturing (AM), and especially laser powder‐bed fusion (LPBF), is constantly growing. Process windows for a large variety of materials are already developed. Nevertheless, some materials are still difficult to manufacture with LPBF. One of these materials is the tungsten carbide/cobalt‐based hard metal (WC–Co), which is conventionally produced by powder metallurgy including liquid‐phase sintering. Most approaches to manufacture WC–Co with LPBF show a high porosity, undesirable phases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The research has extensively covered additive manufacturing of WC-Co hard metals that are produced by powder metallurgy, including conventional liquid-phase sintering [113]. Fries et al processed WC with 17 wt.% Co by laser powderbed fusion (LPBF) with a powder-bed heating of 900 °C [114].…”
Section: Cermets For Additive Manufacturing and Applicationmentioning
confidence: 99%
“…The research has extensively covered additive manufacturing of WC-Co hard metals that are produced by powder metallurgy, including conventional liquid-phase sintering [113]. Fries et al processed WC with 17 wt.% Co by laser powderbed fusion (LPBF) with a powder-bed heating of 900 °C [114].…”
Section: Cermets For Additive Manufacturing and Applicationmentioning
confidence: 99%
“…The occurrence of CC structural defects can be limited in various ways. For example, the formation of cracks can be prevented in the CC structure by increasing the binder content (Khmyrov et al , 2016), by multiple remelting of the powder layer (Fortunato et al , 2019) or by preheating the build platform to high temperatures (Fries et al , 2020). The occurrence of pores can be influenced by the type and quality of the powder used (Chen et al , 2019) and its processing parameters (Uhlmann et al , 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The stainless steel 304 heater holders rest on the stainless steel 304 inner and outer faces connected to stainless steel 304 pillars and the baseplate is bolted to the pillars through the inner face component using M20 mild (low carbon) steel bolts. Studies have shown that using a preheating system minimizes tensile residual stresses [6][7][8][9][10][11][12], therefore improving the quality of the part and reducing part premature failure during building. A 510 Watt Nd-YAG laser was used by Liu et al [6] to preheat yttria-stabilized zirconia ceramics to a maximum temperature of 2500 °C and observe a reduction in vertical cracks and porosity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reviewed had lower build volumes compared to that of the Aeroswift platform, but they had higher heating power compared to the Aeroswift platform since it utilizes 6 kW to heat its current build volume. Calprio et al [10] used 960 W to heat a 38 mm diameter Studies have shown that using a preheating system minimizes tensile residual stresses [6][7][8][9][10][11][12], therefore improving the quality of the part and reducing part premature failure during building. A 510 Watt Nd-YAG laser was used by Liu et al [6] to preheat yttria-stabilized zirconia ceramics to a maximum temperature of 2500 • C and observe a reduction in vertical cracks and porosity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation